الآيات التي روي أنها وردت في الخوارج: دراسة استقرائية تفسيرية - الشغدري، إبراهيم بن عباس بن ناصر (جامعة الإمام محمد بن سعود الإسلامية - الجمعية العلمية السعودية للقرآن الكريم وعلومه, 2022)
هدف البحث: يهدف هذا البحث إلى جمع الآيات التي روي أنها وردت في الخوارج، ودراستها دراسة تفسيرية تجلي علاقة الخوارج بالآية، وتحقيق حجية الروايات الواردة فيها، بيان ماهية تفسير بعض الآيات بالخوارج، وكشف أسباب تلك التفسيرات. واستخدم الباحث المنهج التأصيلي والاستقرائي، وتوصل إلى عدد من النتائج أهمها ما يلي: 1-تفسير بعض الآيات بالخوارج ورد في السنة النبوية وأقوال الصحابة رضي الله عنهم. ٢-ما صح من هذه التفسيرات -مرفوعا أو موقوتا -لا يعني حصر معنى الآية في الخوارج، بل أنهم جزء من المعنى. ٣-لا عجب في صحة روايات عن النبي صلى الله عليه وسلم تفسر آيات بالخوارج، مع كون الخوارج كفرقة ظهروا بعد موت الرسول صلى الله عليه وسلم، وبعد انقطاع الوحي، فهذا يندرج تحت نبوءاته صلى الله عليه وسلم، وهو ضمن أحاديث كثيرة وردت في نعت الخوارج، وذمهم، والتحذير منهم. ٤ -أن مثل هذه التفاسير التي تضمنتها الروايات تنحو ثلاث طرق: التفسير بالعموم، والتفسير بالمثال، والتفسير بالقياس. 5-أن التفسير بالقياس هو الأقل في تلك التفسيرات. ٦-لا يلزم من تفسير آيات بالخوارج تنزيل كل ما رود في الآية بالخوارج، كتنزيل صفات الكفر في الآية عليهم، وهذا واضح في الروايات التي فسرها علي رضي الله عنه بالخوارج، فلم يكن رضي الله عنه يكفرهم، مع أن الآيات تشتمل على بعض صفات الكافرين. فما ينزل من معاني الآية فقط ما يتشارك فيه الخوارج مع الكافرين، من الزيغ، وضلال السعي واتباع المتشابه، ونحو ذلك. ولا يشملهم الصفات الخاصة بالكافرين كالتكذيب بالله ورسله، والتكذيب باليوم والآخر، ونحو ذلك مما لا يكون إلا كفرا. The objective of the research: This research aims to collect the verses that were narrated in the Kharijites sect, and to study them as an interpretative study that demonstrates the relationship of the Kharijites sect to the Qur’anic verse, to achieve the authenticity of the narrations contained therein, to clarify the interpretation of some verses in the Kharijites sect, and to reveal the reasons for these interpretations. The researcher used the original and inductive approach, and reached a number of results, the most important of which are the following: Interpretation of some verses in the Kharijites sect mentioned in the Prophet’s Sunnah and the sayings of the Companions. What is correct from these interpretations- whether raised or suspended- does not mean restricting the meaning of the verse to the Kharijites, but rather that they are part of the meaning. There is no wonder in the authenticity of narrations on the authority of the Prophet Verses are interpreted by the Kharijites, with the Kharijites being a group that appeared after the death of the Messenger, and after the revelation was interrupted, this falls under his prophecies, and it is among many hadiths mentioned in describing the Kharijites, denouncing them, and warning them. To represent these interpretations that were included in the narrations in the manner of three ways: Tafsir in general, exegesis by example, and exegesis by analogy. The interpretation by analogy is the least of those interpretations. Interpretation of verses by the Kharijites is not required to download all that is mentioned in the verse to the Kharijites, such as relegating the characteristics of disbelief to them in the verse to them, and this is evident in the narrations that Ali interpreted وby the Kharijites, so did not disbelieve them, although the verses include some of the characteristics of the unbelievers. What comes down from the meanings of the verse is only what the Kharijites share with the unbelievers, from the aberration, the delusion of seeking and following the similarities, and so on. They are not covered by the characteristics of the unbelievers, such as denial of God and his messengers, denial of the day and the next, and so on, which is nothing but disbelief.
Keywords: القرآن الكريم -- تفسير القرآن -- طائفة الخوارج -- الآيات القرآنية -- السنة النبوية